Granulin Secreted by the Food-Borne Liver Fluke Opisthorchis viverrini Promotes Angiogenesis in Human Endothelial Cells - Haugen, Brandon; Karinshak, Shannon E.; Mann, Victoria H.; Popratiloff, Anastas; Loukas, Alex; Brindley, Paul J.; Smout, Michael J. (Frontiers in Medicine, 2018)
The liver fluke Opisthorchis viverrini is a food-borne, zoonotic pathogen endemic to Thailand and adjacent counties in Southeast Asia. The adult developmental stage of the O viverrini parasite excretes and secretes numerous proteins within the biliary tract including the gall bladder. Lesions caused by the feeding activities of the liver fluke represent wounds that undergo protracted cycles of healing and re-injury over during chronic infection, which can last for decades. Components of the excretory/secretory (ES) complement released by the worms capably drive proliferation of bile duct epithelial cells and are implicated in establishing the oncogenic milieu that leads to bile duct cancer, cholangiocarcinoma (CCA). An ES protein, the secreted granulin-like growth factor termed Ov-GRN-1, accelerates wound resolution in mice and in vitro. To investigate angiogenesis (blood vessel development) that may contribute to wound healing promoted by liver fluke granulin and, by implication, to carcinogenesis during chronic opisthorchiasis, we employed an in vitro tubule formation assay (TFA) where human umbilical vein endothelial cells were grown on gelled basement matrix. Ten and 40 nM Ov-GRN-1 significantly stimulated angiogenesis as monitored by cellular proliferation and by TFA in real time. This demonstration of potent angiogenic property of Ov-GRN-1 bolsters earlier reports on the therapeutic potential for chronic non-healing wounds of diabetics, tobacco users, and the elderly and, in addition, showcases another of the hallmark of cancer characteristic of this carcinogenic liver fluke.